Representation Degree of the first circle pupils of primary teaching to the values of citizenship in the context of the Syrian crisis (A filed study on a sample of pupils in the city of Lattakia) - Barakat, Ghassan; Ali, Wafeka; Younies, Huda (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study aims to determine the degree of representation of the first circle pupils of primary teaching to the values of citizenship in the context of the Syrian crisis according to variables : the kind of staying (A comer pupil -A habitant pupil )and family state (martyr’s son ), but to achieve this, a questionnaire was developed to included(35) paragraphs to measure the degree of representation of the pupils to the values of citizenship , and applied on a sample of (240) pupils. By depending on the suitable statistic ways, the study found that the degree represents pupils for citizenship values were middle , and the highest value was rights and duties and the next was the values of respecting others and acceptation the difference with middle degree ,then the values of belonging, lastly participation and interaction with middle degree the study also found that there is statistically significant difference at the level of significance (α ≥ 0.05) between pupils’ degree on all the axis of the questionnaire according to the variable of the kind of staying exception for the interaction and participation, and it is for emigrants ,and the study also found that there isn’t statistically significant difference at the level of significance (α ≥ 0.05) between pupils’ degree according to the variable of family state.